AN INVESTIGATION INTO STUDENTS’ PISA READING LITERACY PERFORMANCE AND READING ENGAGEMENT - Gita Realita Chintia; Machdalena Vianty; Ida Rosmalina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The objective of this study was to find out reading literacy performance and reading engagement of tenth graders of three public schools in two districts in Palembang based on school location and socioeconomic status (SES). The sample of this study consisted of 254 tenth grade students selected purposively from three public senior high schools in Kemuning and Plaju districts. PISA 2009 Reading Literacy test in English and two questionnaires (reading engagement and SES questionnaires) were used to collect the data, which were analyzed statistically. The finding of this study showed that the students’ PISA reading literacy score in English was 23.39 and it was below the Indonesian Standard of National Education (KKM). It was also at level 3 based on PISA level. In terms of school location, students’ PISA reading literacy score showed significant difference, while in relation to father occupational status which was one of the SES aspects showed that the PISA reading literacy score of the students with white-collar high skilled father and blue-collar low skilled father were different significantly. The results of reading engagement showed that 244 students (96%) had positive attitude toward reading and they stated that they spent 30 minutes or less a day for reading enjoyment as well as have enough time to read online but they rarely spent time reading various types of books in English. In this study, based on school location reading diversity which was one of the aspects of reading engagement showed significant difference.Keywords: effectiveness, genre based approach, teaching English